Battery Recovery Supply Chain Design. a Literature Review - Sepulveda-Salas, J; Espinoza-Perez, A; Santander-Tapia, P (Springer Science and Business Media B.V., 2023)
Batteries are products of many devices, especially electronic ones. The rapid development of electronic devices has reduced the effective life span of these products. As a result, these products end up in landfills and cannot be valorized or used again, causing environmental pollution by the hazardous substances they contain. Currently, it is possible to find different policies and initiatives to increase the percentage of recovered batteries. However, this is a complex process because of its different formats and components. In addition, recovery systems must be developed from a sustainability perspective, which increases their complexity from the perspective of evaluation and implementation. This study presents a literature review to map how the design and implementation of battery recovery supply chains have been addressed in the literature. Fourteen journal articles were selected and analyzed considering the type of problem addressed, the variety of batteries and sustainability dimensions considered, the supply chain studied, the optimization model approach, and the geographical location of the case studies. The main findings are the lack of consideration of social, political, and technological aspects in the sustainability assessment and the lack of consideration of domestic-use batteries. © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.